Genetic programming for structural similarity design at multiple spatial scales - Bakurov, Illya (2022)
Bakurov, I., Buzzelli, M., Castelli, M., Schettini, R., & Vanneschi, L. (2022). Genetic programming for structural similarity design at multiple spatial scales. In GECCO ’22. Proceedings of the 2022 Genetic and Evolutionary Computation Conference (pp. 911-919). (GECCO 2022 - The Genetic and Evolutionary Computation Conference, July 9-13, Boston, US). Association for Computing Machinery (ACM). ISBN 978-1-4503-9237-2/22/07 ---- Funding Information: FCT Portugal partially supported this work, under the grand SFRH/BD/137277/2018, and through projects BINDER (PTDC/CCI-INF/29168/2017) and AICE (DSAIPA/DS/ 0113/2019).